Unilateral Maximal Isometric Hex Bar Pull Test: Within-Session Reliability and Lower Body Force Production in Male and Female Freeski Athletes - McPhail, Jonathan; Gonçalves, Basílio A. M.; Spörri, Jörg; Linnamo, Vesa (Frontiers in Sports and Active Living, 2021)
The aim of the study was to (1) assess the within-session reliability of a unilateral isometric hex bar pull (UIHBP) maximal voluntary contraction (MVC) test and, (2) determine unilateral isometric absolute peak force (PFabs) and relative peak force (PF) values in freeski athletes. Twenty-one male and 8 female academy to national team freeskiers performed the novel UIHBP MVC task on a force plate and PFabs and relative PF were assessed (1000 Hz). Within-session measures of PFabs offered high reliability on left and right limbs for males (ICC=0.91-0.94, CV=2.6-2.2%) and females (ICC=0.94-0.94, CV=1.4-1.6%), while relative PF measures showed good to high reliability in both left and right limbs for males (ICC=0.8-0.84, CV=2.6-2.2%) and females (ICC=0.92-0.90, CV=1.4-1.7%). We observed significantly lower PFabs (P<0.001) and relative PF (P<0.001) in females compared to males. No statistical difference was found between left and right limbs in males and females in PFabs (P=0.98) and relative PF measures (P=0.93). The UIHBP MVC test appears to be a reliable method for assessing PFabs and relative PF in male and female freeski athletes.